Direct rapid prototyping evaluation on multijet and fused deposition modeling patterns for investment casting - Marwah, Omar Mohd Faizan (Sage Journals, 2016)
The continuation from rapid prototyping into rapid tooling technologies allows speedy fabrication of sacrificial patterns for investment casting process. Direct expendable pattern fabrication with intricate features using rapid prototyping techniques significantly reduces the fabrication cost when associated with single- or low-volume production. During investment casting process, rapid prototyping patterns are subjected to high melting temperatures, high viscosities, and high thermal stress such as dewaxing and shell mold cracking. Furthermore, ceramic shell may cause crack during melting and burning out of the patterns and also incomplete collapsibility. Although rapid prototyping process can build parts with high stiffness rapidly, the part surface suffered a staircase effect and shrinkage during investment casting process solidification. This paper presents a direct approach of multijet modeling and fused deposition modeling on acrylate- and acrylonitrile–butadiene–styrene-based materials to be used as expendable patterns for the investment casting process. Thermal analyses were conducted on the rapid prototyping materials that exhibit mass loss and expansion. Quality assessment and benchmarking were performed between the rapid prototyping and the metal part on accuracy, surface roughness, and part built time. It was found that both the materials have dimensional deviation when employed in investment casting process and acrylate patterns have better surface roughness as compared to acrylonitrile–butadiene– styrene patterns. Additionally, multijet modeling recorded a significantly shorter lead time when more than a single part can be produced during the rapid prototyping process. It was observed that the shell mold after burnout experiences cracking. Results also showed that acrylate-based materials decomposed above 500°C, meanwhile acrylonitrile– butadiene–styrene was above 600°C. Acrylate material had a coefficient of thermal expansion and linear dimensional deviation as compared with acrylonitrile–butadiene–styrene. No ash was observed in the ceramic molds when the part burnout temperatures are above 500°C acrylate material and 600°C for acrylonitrile–butadiene–styrene.